2010
DOI: 10.1016/j.fertnstert.2010.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Potential diagnostic utility of intermittent administration of short-acting gonadotropin-releasing hormone agonist in gonadotropin deficiency

Abstract: Objective-The objective was to determine if intermittent, low-dose, short-acting GnRH agonist (GnRHag) administration up-regulates pituitary-gonadal function in gonadotropin deficiency (GnD) sufficiently to be of diagnostic or therapeutic value.Design/Intervention-Low-dose leuprolide acetate was administered SC at 4-5 d intervals up to one year.Patients-Adult volunteers and GnD patients were studied.Setting-The studies were performed in a General Clinical Research Center. Main Outcome Measures-LH, FSH, and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In consultation with our endocrinologists, we determined that both assays are analytically and clinically equivalent, and the existing reference intervals established by the classic RIA method developed in our institution and published by our endocrinologists in the literature (34)(35)(36)(37)(38) are transferrable to the LC-MS/MS assay. The bias of this assay at the LOQ level was also not assessed, since there are currently no low E 2 reference materials available, and bias study by spiking standards and serially diluting up to 200-fold could result in large variation at the low end.…”
Section: Limitationsmentioning
confidence: 99%
“…In consultation with our endocrinologists, we determined that both assays are analytically and clinically equivalent, and the existing reference intervals established by the classic RIA method developed in our institution and published by our endocrinologists in the literature (34)(35)(36)(37)(38) are transferrable to the LC-MS/MS assay. The bias of this assay at the LOQ level was also not assessed, since there are currently no low E 2 reference materials available, and bias study by spiking standards and serially diluting up to 200-fold could result in large variation at the low end.…”
Section: Limitationsmentioning
confidence: 99%
“…This important observation led Plant and colleagues [64,65,66,67,68]to employ a standard GnRH priming protocol in their studies where gonadotropin secretion is measured in response to various factors. Studies have also been conducted in men exhibiting gonadotropin deficiency, and in the absence of any pituitary defects it has been reported that GnRH priming improves gonadotropin secretion [69,70]. More detailed studies in human male patients are generally lacking because males who are diagnosed with GnRH and gonadotropin deficiency often exhibit pituitary and testicular defects [71].…”
Section: Kiss1r Displays Basal Constitutive Signaling and Kp-independmentioning
confidence: 99%
“…LH pulse amplitude is also increased (Kazer et al, 1987; Waldstreicher et al, 1988), which is reflected in the size of the pulse induced promptly by GnRH (Arroyo et al, 1997) or GnRH agonist administration (Barnes et al, 1989). LH secreted early (30–60 min) in response to GnRH or GnRH agonist injection subcutaneously represents the readily releasable gonadotrope pool of preformed LH (GnRH agonist, being long-acting, then stimulates synthesis and release of a second, slowly releasable gonadotropin pool) (Bremner and Paulsen, 1974; Redding et al, 1972; Rosenfield et al, 1996; Zimmer et al, 2010). …”
Section: Relationship Of Nutritional Status To Neuroendocrine Funcmentioning
confidence: 99%
“…There is also a sexual dimorphism in gonadotropin production that indicates a net testosterone stimulatory effect on LH pulse amplitude in response to GnRH (Rosenfield et al, 1996; Zimmer et al, 2010). Normal men have a higher LH response than women within the first hour after a GnRH agonist injection, although baseline LH levels are similar between the sexes; then men’s LH plateaus.…”
Section: The Relationship Of Androgen Status To Neuroendocrine Funmentioning
confidence: 99%